The Use of a Desk-top Computer for Routine Calculations in a Clinical Radioisotope Laboratory - Roos, P. (Nuklearmedizin - NuclearMedicine, 1969)
The usefulness of a desk-top computer for routine calculations in a clinical radioisotope laboratory is demonstrated. Main advantages are a large gain in time and an increase in precision. Examples of calculations presented include 131I thyroid function tests in vivo and in vitro, determination of the apparent half-life of 51Cr-marked erythrocytes, radioimmunoassay of serum insulin levels, saturation analysis of serum vitamin B12 levels and a few special programs having a wide applicability.